"Double-Hit" Mature B-Cell Lymphomas Show a Common Immunophenotype by Flow Cytometry That Includes Decreased CD20 Expression. Issue 2 (August 2015) - Wu, David; Wood, Brent L.; Dorer, Russell; Fromm, Jonathan R.
Abstract : Lymphomas with 2 translocations involving c- MYC and BCL2 or BCL6 are a subset of biologically aggressive mature B-cell lymphomas now frequently categorized under the entity of B-cell lymphoma, unclassifiable, with features intermediate between Burkitt lymphoma and diffuse large B-cell lymphoma. We identified a cohort of these lymphomas in our databases and retrospectively reviewed corresponding in-house flow cytometric data to determine whether a common immunophenotype might be present. Herein we report on our findings on 10 lymphomas, each with translocations involving c- MYC and BCL2 or BCL6 and show that these cases frequently showed a common immunophenotype that includes decreased expression of CD20. Because these lymphomas often show aggressive biologic behavior and poor clinical outcome, recognition of this relatively common immunophenotype may be useful for identifying cases for confirmatory cytogenetic studies, as often, flow cytometry provides the first assessment of these clinical specimens.